2009
DOI: 10.1590/s0102-76382009000100003
|View full text |Cite
|
Sign up to set email alerts
|

Resultados da abordagem transeptal para a valva mitral com coração batendo

Abstract: Results of beating heart mitral valve surgery via the trans-septal approachResultados da abordagem transeptal para a valva mitral com coração batendo Resumo Objetivo: A cirurgia da valva mitral pode ser feita via transatrial ou transeptal. Embora a transatrial seja a preferida, a via transeptal tem sido utilizada mais recentemente e tido um grande valor nas operações com o coração batendo. Mostramos a nossa experiência na cirurgia da valva mitral via transeptal com coração batendo e discutimos seus benefícios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Best surgical times, not compromised venous drainage and repair of the septum by periods of traction without the need for atrial retractors were observed and reported in summary of study presented by our team in recent conference [42]. In surgery with sternotomy, this access has also been reviewed, offering the same benefits that we observed [43]. Navia et al [30], in their report with minimally invasive surgery in 1996 had demonstrated the use of the transseptal access in their procedures for treatment of mitral valve.…”
Section: Discussionmentioning
confidence: 60%
“…Best surgical times, not compromised venous drainage and repair of the septum by periods of traction without the need for atrial retractors were observed and reported in summary of study presented by our team in recent conference [42]. In surgery with sternotomy, this access has also been reviewed, offering the same benefits that we observed [43]. Navia et al [30], in their report with minimally invasive surgery in 1996 had demonstrated the use of the transseptal access in their procedures for treatment of mitral valve.…”
Section: Discussionmentioning
confidence: 60%
“…Santana Filho evaluated patients undergoing mitral valve replacement with crossed papillopexy with echocardiography 30. Salerno et al described the results of beating heart mitral valve surgery via the trans-septal approach 31. Dalva et al described initial results of intermittent annular reduction with Alfieri’s repair for the treatment of mitral insufficiency in children 32.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of a minor aortic leak can significantly interfere with the exposure and the course of the procedure. Salerno used a trans-septal approach for clampless beating heart mitral valve surgery in 214 patients to reduce aortic insufficiency and improved visualization of the mitral apparatus [20]. To counteract this discomfort, Ricci published a technique for continuous coronary perfusion, combining the retrograde and anterograde routes with aortic cross-clamping, which allowed him to perform beating heart polyvalvular surgery [21].…”
Section: ) Advantages Of This Techniquementioning
confidence: 99%